2019
DOI: 10.1007/s00401-019-02059-z
|View full text |Cite
|
Sign up to set email alerts
|

MSTO1 mutations cause mtDNA depletion, manifesting as muscular dystrophy with cerebellar involvement

Abstract: MSTO1 encodes a cytosolic mitochondrial fusion protein, misato homolog 1 or MSTO1. While the full genotype–phenotype spectrum remains to be explored, pathogenic variants in MSTO1 have recently been reported in a small number of patients presenting with a phenotype of cerebellar ataxia, congenital muscle involvement with histologic findings ranging from myopathic to dystrophic and pigmentary retinopathy. The proposed underlying pathogenic mechanism of MSTO1-related disease is suggestive of impaired mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
(97 reference statements)
1
32
0
Order By: Relevance
“…The reduced mtDNA copy number and nucleoid number observed in patient fibroblasts is consistent with impaired mitochondrial fusion in these cells, as reduced copy number is proposed to be due to inefficient fusion-dependent distribution of the mtDNA replication machinery (19). Surprisingly, we also observed slightly smaller nucleoids in patient cells, an unexpected finding given that impaired mitochondrial fusion has previously been linked to enlarged mitochondrial nucleoids (19,21,64). However, it should be noted that it is not clear why nucleoid size increases in response impaired fusion.…”
Section: Discussionsupporting
confidence: 85%
“…The reduced mtDNA copy number and nucleoid number observed in patient fibroblasts is consistent with impaired mitochondrial fusion in these cells, as reduced copy number is proposed to be due to inefficient fusion-dependent distribution of the mtDNA replication machinery (19). Surprisingly, we also observed slightly smaller nucleoids in patient cells, an unexpected finding given that impaired mitochondrial fusion has previously been linked to enlarged mitochondrial nucleoids (19,21,64). However, it should be noted that it is not clear why nucleoid size increases in response impaired fusion.…”
Section: Discussionsupporting
confidence: 85%
“…It has been reported that TFAM and mtDNA stabilize each other by binding to each other; thus, mtDNA can only be stably maintained in the form of nucleoid structures within the mitochondria, whereas both naked DNA and free TFAM in mitochondria are unstable and can be rapidly degraded 34 . During disease development, decreased TFAM levels may impair the interaction of TFAM with mtDNA and thus reduce the number of nucleoids and cause the formation of aberrant clusters; this, in turn, results in depletion of mtDNA and inhibition of mitochondrial transcription 55 , 56 . Indeed, we found that TFAM knockdown alone was sufficient to induce mtROS production, aberrant packaging of mtDNA nucleoids, and mitochondrial respiratory defects in TECs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients from 15 families were previously published as part of a brief report on utility of WES in pediatric-onset ataxia and in separate publications reporting novel genes or expanding the phenotypic spectrum associated with known genes. [14][15][16][17][18][19][20][21][22][23] WES was performed on total genomic DNA from the 92 participants. DNA was extracted from peripheral blood following standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Patients from 15 families were previously published as part of a brief report on utility of WES in pediatric‐onset ataxia and in separate publications reporting novel genes or expanding the phenotypic spectrum associated with known genes 14–23 …”
Section: Methodsmentioning
confidence: 99%